2011
DOI: 10.1002/etc.679
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological impact of the fungicide tebuconazole on an aquatic decomposer‐detritivore system

Abstract: Leaf litter breakdown is a fundamental process in aquatic ecosystems that is realized by microbial decomposers and invertebrate detritivores. Although this process may be adversely affected by fungicides, among other factors, no test design exists to assess combined effects on such decomposer-detritivore systems. Hence, the present study assessed effects of the model fungicide tebuconazole (65 µg/L) on the conditioning of leaf material (by characterizing the associated microbial community) as well as the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 39 publications
6
90
2
1
Order By: Relevance
“…This apparent lack of TBZ effect on heterotrophic microbial communities colonizing alder leaves is inconsistent with most previous studies and Artigas et al, 2012. Since the exposure duration used here (40 days) was comparable to that used by Artigas et al (2012) and longer than the roughly two weeks used in Zubrod et al (2011) and , the absence of drastic effects in the present study could be linked to the use of a lower TBZ concentration (average concentrations of 17.1 µg L−1) compared to those previous studies, where nominal or measured TBZ concentrations ranged from 33 up to 500 µg L−1. Note, however, that the comparison of exposure level between studies is rendered difficult by the differences in experimental systems and procedures conditioning the dynamics of dissolved TBZ whose concentrations fluctuate over time (due to adsorption, absorption and desorption phenomena), as shown here.…”
Section: Effects Of Individual Stressors On Microbial Leaf Litter Deccontrasting
confidence: 93%
See 1 more Smart Citation
“…This apparent lack of TBZ effect on heterotrophic microbial communities colonizing alder leaves is inconsistent with most previous studies and Artigas et al, 2012. Since the exposure duration used here (40 days) was comparable to that used by Artigas et al (2012) and longer than the roughly two weeks used in Zubrod et al (2011) and , the absence of drastic effects in the present study could be linked to the use of a lower TBZ concentration (average concentrations of 17.1 µg L−1) compared to those previous studies, where nominal or measured TBZ concentrations ranged from 33 up to 500 µg L−1. Note, however, that the comparison of exposure level between studies is rendered difficult by the differences in experimental systems and procedures conditioning the dynamics of dissolved TBZ whose concentrations fluctuate over time (due to adsorption, absorption and desorption phenomena), as shown here.…”
Section: Effects Of Individual Stressors On Microbial Leaf Litter Deccontrasting
confidence: 93%
“…The mode of action of TBZ relies on the inhibition of the biosynthesis of ergosterol, a sterol essential for the functioning of fungal cells due to its role in cell membrane permeability and fluidity. The reported impacts of TBZ on microbial communities can also induce indirect effects on leaf shredding invertebrates due to the reduction in palatability and nutritional quality of leaf resources Zubrod et al, 2011). TBZ can also have direct sublethal effects on shredders, especially inhibition of feeding activity (Zubrod et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The triazole fungicide tebuconazole interacts, amongst others, with 14-a-demethylase (i.e., demethylation inhibitor), which is fundamental in the transformation pathways of lanosterol to ergosterol in fungi but also cholesterol in animals (Stenersen 2004). Although the underlying mechanisms are not fully understood, triazole fungicides adversely affect nontarget species by decreasing their activity (Sancho et al 2009;Zubrod et al 2010) and, finally, their trophic interactions, as shown for a decomposer-detritivore system involved in leaf-litter breakdown Zubrod et al 2011). The pyrethroid lambda-cyhalothrin, in contrast, interacts directly with the nervous system causing a continuous impulse transmission along axons by binding to proteins regulating the voltage-gated sodium channel (He et al 2008;Stenersen 2004).…”
mentioning
confidence: 97%
“…Fungicides used for plant disease control are frequently detected in stream ecosystems and are widespread in vineyard areas Battaglin et al 2011). Their impacts on the structure and function of fungal communities involved in leaf litter decomposition can have profound effects on aquatic ecosystem functioning (Zubrod et al 2011;Artigas et al 2012). Such effects emphasize the need for the use in further research of functional endpoints associated with fungal communities to assess potential impacts of fungicide on aquatic ecosystems.…”
Section: Discussionmentioning
confidence: 99%